2020
DOI: 10.1016/j.isci.2020.101855
|View full text |Cite
|
Sign up to set email alerts
|

Role of SPTSSB-Regulated de Novo Sphingolipid Synthesis in Prostate Cancer Depends on Androgen Receptor Signaling

Abstract: Anti-androgens are a common therapy in prostate cancer (PCa) targeting androgen receptor (AR) signaling. However, these therapies fail due to selection of highly aggressive AR-negative cancer cells that have no therapeutic options available. We demonstrate that elevating endogenous ceramide levels with administration of exogenous ceramide nanoliposomes (CNLs) was efficacious in AR-negative cell lines with limited efficacy in AR-positive cells. This effect is mediated through reduced de novo sphingolipid synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…Phosphate esters such as PC and PE are the main components of cell membranes, and changes in their chain length can directly cause changes in membrane fluidity, which in turn affects membrane permeability, material transport, and the localization of membrane proteins ( Chen et al, 2018 ; Galbraith et al, 2018 ; Di Mitri et al, 2019 ; Watt et al, 2019 ; Blomme et al, 2020 ; Centenera et al, 2021 ). Sphingolipids are also involved in cancer cell biology at multiple levels ( Furuya et al, 2011 ; Costa-Pinheiro et al, 2020 ; Vykoukal et al, 2020 ; Lin et al, 2021a ; Lin et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate esters such as PC and PE are the main components of cell membranes, and changes in their chain length can directly cause changes in membrane fluidity, which in turn affects membrane permeability, material transport, and the localization of membrane proteins ( Chen et al, 2018 ; Galbraith et al, 2018 ; Di Mitri et al, 2019 ; Watt et al, 2019 ; Blomme et al, 2020 ; Centenera et al, 2021 ). Sphingolipids are also involved in cancer cell biology at multiple levels ( Furuya et al, 2011 ; Costa-Pinheiro et al, 2020 ; Vykoukal et al, 2020 ; Lin et al, 2021a ; Lin et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Phase I clinical trial of the patented LipC6 has been recently completed (NCT#02834611). 40 Our recent studies led to the new findings that LipC6 has the capacity to break HCC-induced immune tolerance. 17 Of particular importance, we have now demonstrated that LipC6 treatment significantly improves αCTLA-4 Ab's therapeutic suppression on HCC.…”
Section: Molecular Events In Association With T Cell Activation Induc...mentioning
confidence: 99%
“…ssSPT subunits have been described as important regulators of SPT activity. Recently, it has been observed that in patients with prostate cancer treated with anti-androgens treatment, an increase in the expression of SPTSSB was detected [ 70 ]. Moreover, administration of exogenous Cer nanoliposomes was determined as an efficient treatment in cancer cells [ 70 ].…”
Section: Enzymes Of Ceramide Metabolismmentioning
confidence: 99%
“…Recently, it has been observed that in patients with prostate cancer treated with anti-androgens treatment, an increase in the expression of SPTSSB was detected [ 70 ]. Moreover, administration of exogenous Cer nanoliposomes was determined as an efficient treatment in cancer cells [ 70 ]. In addition to ssSPT subunits, the Tsc3 subunit was found to be a potent regulatory protein of SPT, increasing its activity by up to 50-fold [ 71 , 72 ].…”
Section: Enzymes Of Ceramide Metabolismmentioning
confidence: 99%